2009
DOI: 10.2147/tcrm.s4823
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic seizure after treatment with thiocolchicoside

Abstract: Background:Adverse drug reactions are important determinants of inpatient and outpatient morbidity. Thiocolchicoside is a semisynthetic derivate of naturally occurring colchicoside, which is largely used in humans as a centrally acting muscle relaxant. Epileptic seizures after thiocolchicoside intake have been reported in individuals with a history of epilepsy, acute brain injury or possible blood–brain barrier disruption.Case report:We report the case of a 66-year-old male patient presenting a sudden epilepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Several neurological side effects have been reported in association with TCC treatment including somnolence, confusion and seizure, the latter in a low percentage of patients. 3 However, a major epileptological complication, such as status epilepticus, has never been previously reported in association with TCC treatment. In the present report, we described a case of acute refractory NCSE in the context of a TCC‐induced acute toxic encephalopathy (ATE) in a woman without any previous neurological or physical comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several neurological side effects have been reported in association with TCC treatment including somnolence, confusion and seizure, the latter in a low percentage of patients. 3 However, a major epileptological complication, such as status epilepticus, has never been previously reported in association with TCC treatment. In the present report, we described a case of acute refractory NCSE in the context of a TCC‐induced acute toxic encephalopathy (ATE) in a woman without any previous neurological or physical comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…2 Even though the mechanism of action of TCC is not yet well understood, previous studies have suggested the interaction of this compound with a cortical subtype of the gamma-aminobutyric acid type A (GABA-A) receptor, inhibiting GABAergic transmission. 3 This peculiar mechanism could explain its pro-epileptogenic properties. In fact, TCC was described to reduce seizure threshold and cause convulsions in rat models.…”
Section: Introductionmentioning
confidence: 99%
“…One of these studies showed TCC-induced seizure following disturbances of the blood-brain barrier (BBB), which indicates that TCC should be avoided in patients with BBB disruption (15). A second study reports a patient with a diagnosis of cerebral amyloid angiopathy, which disrupts the BBB, and the association with TCC treatment for muscle contracture and pain resulted in seizures (17). A third study involved a healthy 3-month-old patient who had a seizure after her mother had taken TCC while breastfeeding (16).…”
Section: Discussionmentioning
confidence: 99%
“…There are some case reports of TCC-induced seizures in human patients (15)(16)(17)(18). Specific experimental or clinical conditions proved that TCC could induce seizures especially in neurological patients with a history of epilepsy (12,15).…”
Section: Introductionmentioning
confidence: 99%
“…It is chemically 2-demethoxy-2-glucosidoxythiocolchicine with a chemical formula C 27 H 33 NO 10 S. TCC has been used clinically for humans as a centrally acting muscle relaxant agent for the treatment of orthopedic, traumatic and rheumatological disorders [5]. This compound also has anti-inflammatory and analgesic effects [6]. It is an analogue of colchicines, since they share the same benzo(alpha) heptalenic moiety [7].…”
Section: Introductionmentioning
confidence: 99%